2009
DOI: 10.1159/000197900
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Traumatic Peripheral Nerve Injuries and Amputations in Sweden between 1998 and 2006

Abstract: Background: To define the epidemiological pattern of nerve injuries and traumatic amputations in Sweden, 1998–2006, and investigate possible targets for emerging neural engineering and neuroprosthetic technologies. Methods: The Swedish Hospital Discharge Register was used as the information base, including data from all public inpatient care, excluding outpatient data. ICD-10 codes were used to classify nerve injuries and traumatic amputations of high incidence levels or inpatient care time. Selected codes, ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
81
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(87 citation statements)
references
References 66 publications
3
81
0
3
Order By: Relevance
“…In addition, women are not accustomed to riding motorcycle in Iran. [4] Our study showed that 90% of the trauma patients were under 50 years old, and the peak frequency of PNI was identified in the 21-30-year-old age group, which shows the higher vulnerability of the youth. [9,10,13,17] Lower ISS and hospital stay were both suggestive of less severity of trauma in PNI patients versus those without nerve injury.…”
Section: Length Of Hospital Stay and Expensesmentioning
confidence: 78%
See 2 more Smart Citations
“…In addition, women are not accustomed to riding motorcycle in Iran. [4] Our study showed that 90% of the trauma patients were under 50 years old, and the peak frequency of PNI was identified in the 21-30-year-old age group, which shows the higher vulnerability of the youth. [9,10,13,17] Lower ISS and hospital stay were both suggestive of less severity of trauma in PNI patients versus those without nerve injury.…”
Section: Length Of Hospital Stay and Expensesmentioning
confidence: 78%
“…Data from developed countries are useful but insufficient for strategic long-term planning in developing countries. [4] In this study, the incidence of PNI and the related factors in trauma patients in Iran are discussed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…for tumor excision lesion (Evans, 2001;Siemionow and Brzezicki, 2009;Isaacs, 2013). Although usually not threatening the patient's life, nerve injuries represent a heavy social burden in terms of both long term disability and economic costs (Asplund et al, 2009;Rosberg et al, 2013). For this reason, growing efforts are dedicated to the development of effective treatment for peripheral nerve injuries which increase tissue regeneration and functional recovery and might be eventually translated to the patients for improving the clinical outcome (Tos et al, 2013, Griffin et al, 2013.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, other studies have reported that the majority of PNIs occurred in the wrist and hand region (20). Saadat and colleagues (21) reported the forearm to be the most frequently involved area, followed by the wrist and hand.…”
Section: Discussionmentioning
confidence: 97%